The injured motor cycle messenger. Issue 3 (September 1993) - Sweetnam, D I; Morris, F; Cope, A
Abstract : Injured motor cycle messengers make up a small but significant proportion of the young injured attending Central London accident and emergency (A&E) departments. The study confirms that the pattern of their injuries is similar to other injured urban motor cyclists, and discusses the background of the injured, in terms of experience and training, highlighting the frequency of injury and possible predisposing factors. A total of 116 injured motor cycle messengers attending two Central London A&E departments over a 10-month period were studied. Thirteen per cent sustained sufficiently serious injuries to necessitate admission, the rest were treated as out-patients for lesser injuries. The mean age was 23. Only 18% had received any formal training and 31% were in possession of a provisional driving license only. Fifty-eight per cent had been employed as a messenger for less than 3 months, yet two-thirds of them had sustained a previous injury whilst a messenger. The apparent absence of supervision of this potentially dangerous occupation is emphasized. In view of the repeated injuries sustained by many of these vulnerable young men, it is suggested that those responsible for their treatment might, in addition to their therapeutic role, give suitable guidance that might prevent re-attendance with further injuries.